TEACHER TALK IN THE CLASSROOM INTERACTION BY USING FIACS AT SMP NEGERI 37 MEDAN - Aspita Zega; Yeni Erlita (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2023)
This study aimed to investigate the types of teacher’ talk that occurs in English classroom interaction and to investigate the teacher’ reasons to use the types of categories in classroom interaction. This study focuses on analyzing the process of classroom interaction through Flanders Interaction Analysis Categories System (FIACS). This study was conducted by using descriptive qualitative research. It was conducted in SMP Negeri 37 Medan at the VII-D grade class.  The subject of this research was an English teacher in SMP Negeri 37 Medan. The observation, recording, and interview techniques were used to collect the data. According to the findings of the study, the English teacher used all categories based on category of FIACS. The types of teacher talk that occurred were accept feeling, praises and encouragement, accepts’ or uses ideas of students, asking question, lecturing, giving direction and criticizing or justifying authority. The reasons why the teacher’ used that types of categories in classroom interaction.  Accept Feelings, the teacher used that type is to help students be bolder in expressing their ideas or opinions. Praise or Encourages, the teacher used that type is to make students can feel appreciated. Praised given by the teacher can make students confident to interact in the classroom. Uses student idea, the teacher used that type is to develop ideas or suggestions given by students. Asking Questions, the teacher used that type because the teacher wants to hone students’ skill and to make students’ understood about the topic being discussed before getting into the next topic. Lecturing, the teacher used lecturing in the classroom during teaching and learning process to make process of teaching and learning in the classroom to be successful. Giving Direction, the teacher used that type because the teacher’ want to know whether the students understand about the material or not. Criticizing or justifying authority, the teacher used that type is to create comprehensible condition for students to acquire target language. Keywords: Teacher Talk, Flanders Interaction Analysis Categories